Analysis of Factors Affecting the Performance of Stock and Bond-Based ETF on The Indonesia Stock Exchange - Christi, Eva Aprilia; Sihombing, Pardomuan (Jurnal Manajemen, 2023)
This study aims to determine the analysis of factors that affect the performance of stock and bond-based ETFs on the Indonesian stock exchange. This research was conducted on stock and bond-based ETFs listed on the Indonesian stock exchange for the period 2019-2021. The sampling technique used in this research is purposive sampling. The samples in this study were 13 stock-based ETFs and 1 bond-based ETF sourced from Bloomberg, the Indonesian stock exchange website, ETF prospectus and asset management website. The data analysis method used is panel data regression analysis with the EViews program tool. The results of this study indicate that Risk affects the performance of stock and bond-based ETFs, Tracking Errors affect the performance of stock and bond-based ETFs, Expense Ratio has no significant impact on the performance of stock and bond-based ETFs. Key Words: ETFs, Risk, Tracking Error, Expense Ratio, Stock, Bond